DIGITALISASI PENGELOLAAN KETERLAMBATAN PEMBAYARAN KONTRIBUSI RT BERBASIS INOVASI INDUSTRI 4.0" - Syamsudin Syamsudin; Sartono Sartono; Yogi Priyo Istiyono; Abu Naim; Raden Hernadi; Rahman Soesilo; Nirfison Nirfison; Ulfa Medianti (Jurnal Abdimas Bina Bangsa, 2024)
Neighborhood Association dues are financial income collected every month from residents which are collected from the beginning of the month until usually the 20th of each month. The money from the Neighborhood Association contributions is used for security guard honorariums, donations from sick residents, and other activities. Some of the obstacles faced by fee collection officers are: Difficulty meeting with residents, residents making promises but not keeping payments and neighborhood association fees not being collected on time. To overcome this, we apply a transfer method for the contribution payment process. An account is created from BCA bank in the names of the RT Head and Treasurer. For the transfer process so that there are no additional costs, we socialize the Flip application as a transfer medium. After carrying out socialization, workshops and trial running, good results were obtained, namely the time for collecting contributions was shorter